Gamete quality in a multistressor environment. (May 2020) - Gallo, Alessandra; Boni, Raffaele; Tosti, Elisabetta
Highlights: State of knowledge on environmental stressors impact on gamete quality. Xenobiotics, plastics, climate change, air pollution and lifestyle are reviewed. Gamete quality parameters underling fertilization competence are susceptible to stressors. Environmental stressors represent a serious hazard to gamete quality. Gamete quality impairment may reduce reproductive success affecting specie fitness and survival. Abstract: Over the past few decades, accumulated evidence confirms that the global environment conditions are changing rapidly. Urban industrialization, agriculture and globalization have generated water, air and soil pollution, giving rise to an environment with a growing number of stress factors, which has a serious impact on the fitness, reproduction and survival of living organisms. The issue raises considerable concern on biodiversity conservation, which is now at risk: it is estimated that a number of species will be extinct in the near future. Sexual reproduction is the process that allows the formation of a new individual and is underpinned by gamete quality defined as the ability of spermatozoa and oocytes to interact during fertilization leading to the creation and development of a normal embryo. This review aimed to provide the current state of knowledge regarding the impact of a broad spectrum of environmental stressors on diverse parameters used to estimate and evaluate gamete quality in humans and in canonical animal models used for experimental research. Effects of metals, biocides, herbicides, nanoparticles, plastics, temperature rise, ocean acidification, air pollution and lifestyle on the physiological parameters that underlie gamete fertilization competence are described supporting the concept that environmental stressors represent a serious hazard to gamete quality with reproductive disorders and living organism failure. Although clear evidence is still limited, gamete capacity to maintain and/or recover physiological conditions is recently demonstrated providing further clues about the plasticity of organisms and their tolerance to the pressures of pollution that may facilitate the reproduction and the persistence of species within the scenario of global change. Changes in the global environment must be urgently placed at the forefront of public attention, with a massive effort invested in further studies aimed towards implementing current knowledge and identifying new methodologies and markers to predict impairment of gamete quality.